PENGARUH FLAVONOID PROPOLIS TERHADAP LAMA PENYEMBUHAN LUKA BAKAR GRADE II PADA TIKUS PUTIH - Herin Mawarti (STRADA : Jurnal Ilmiah Kesehatan, 2012)
Propolis to main content flafonoid have antioxidant properties, anti-inflammatory and antibiotic believed to be used as an agent in wound healing. The purpose of this study is to prove the effect of propolis on the healing process of burns . The research was carried out in vivo with a sample of 21 rats . Maintenance of experimental animals for 14 days were divided into three treatment groups : (1 ) Giving bioplasenton; ( 2 ) treatment of propolis 1 time a day, (3 ) treatment of propolis 2 times a day. Observation of wound healing observed changes in the diameter of the wound seen in the inflammatory phase – 4 days and the proliferative phase at day -14 . In addition to the observed changes in the diameter of the wound healing and duration until wound is drying . The results showed no significant difference in the diameter of the third group wound treatment, burns and diameter significantly at day -14 ( p = 0.001 ). where the diameter of the wound 3 groups of almost equal groups of 1 were given the drug bioplasenton. Wound healing differed significantly in all three treatment groups and the wound healing process in awarding propolis almost equal to 2 times bioplasenton drug delivery . Results of this study demonstrate that administration of propolis 2 times a day have an influence on wound healing drug delivery bioplasenton almost equal compared to administration of propolis 1 a day. Advised to examine wound healing by microscopic observation of the histological observed and advised to observe the wound healing process through the stages of wound closure.